Bio‐tribological characterisation of ultra‐high molecular weight polyethylene against different metal counterparts. Issue 2 (11th May 2022) - Xin, Hua; Liang, Haitao; Zhang, Lei; Jia, JunHong; Li, Xiashuang; Jin, Zhongmin
Abstract: Excessive wear is a key issue affecting the performance of ultra‐high molecular weight polyethylene (UHMWPE)‐based artificial prosthesis. This work is focussed on the bio‐tribology behaviours of UHMWPE when mating with different metal counterparts (iron‐based 316L, Co‐based Stellite‐S21 and Stellite‐S22). According to the ASTM F732 standard, two million cycles comparative wear tests were carried out under bovine serum lubrication. When coupled with S21, S22, and 316L metal counterparts, the obtained average wear factors of UHMWPE were 1.333 ± 0.192, 1.360 ± 0.160, and 1.190 ± 0.177 × 10 −6 mm 3 /N · m, respectively. Initial surface roughness of the metal counterpart has shown an important role in controlling the volume of UHMWPE wear, especially the first one million cycles. Compared with 316L, CoCrMo‐based counterparts possessed relative higher hardness and exhibited less rise in surface roughness caused by wear. For UHMWPE‐on‐metal bearings, random scratch, surface pit, and wear debris attachment were commonly seen, which suggested the coexistence of abrasion, third‐body abrasion, and adhesion‐based wear. In contrast, the metal counterpart was slightly scratched with no polymer transfer film formation. The work conducted in the present study gives useful knowledge regarding the UHMWPE‐on‐metal bearing design. With an intention to minimise wear, surface roughness of metal counterpart should be carefully controlled.